Early Christian English teachers in Korea: Imperialists or advocates? Exploring the lesser known other truth - Wong, Mary Shepard (International journal of Christianity & education, 2018)
Education has long been an interest of foreign missionaries. Many criticisms have been raised over the promotion of imperialism in foreign missionary education. However, what is often overlooked is the positive mutual impact foreign educators have had on both their host and home societies. This article explores the influence of early educational missionaries in Korea and considers the other truth of the positive impact they had as advocates for Koreans during the Japanese colonial period. After a historical overview, the authors highlight missionary contributions to social justice and the restoration of Korean national spirit. They conclude with implications for today.